If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(60-(5*x))/2 = (40-(3*x))/2 // - (40-(3*x))/2
(60-(5*x))/2-((40-(3*x))/2) = 0
(60-5*x)/2-((40-3*x)/2) = 0
(60-5*x)/2+(-1*(40-3*x))/2 = 0
60-1*(40-3*x)-5*x = 0
20-2*x = 0
(20-2*x)/2 = 0
(20-2*x)/2 = 0 // * 2
20-2*x = 0
20-2*x = 0 // - 20
-2*x = -20 // : -2
x = -20/(-2)
x = 10
x = 10
| (60-5X)/2 | | 9x-3=12+12x | | X/2-7=14 | | 20t^2+7t-6=0 | | 9x^2-2.1x+0.1=0 | | -2x-8-3x-2=-2-6x-2 | | x+18=4x-9 | | x+18=4x+9 | | 1/2a=-6 | | 2+1/3y=1 | | 8x+4-29=6x-15 | | 2/3(9x-15) | | 9*35= | | 13=y-3 | | 8y^3+24y^2-7=0 | | m^3+m^2-3m=0 | | 3b+2b-6=14 | | 1/2s-20=-16 | | f(x)=4.5x-2lnx | | 5x-34(x+1)=2(x+3)-5 | | 4-2y=3y-1 | | 7x-4=69 | | 7x-4=58 | | ((x-5)/(8))*(8x+5) | | 6+1/2=x | | (x/3)-4=x-2 | | 6x^2*2x-1=0 | | -9(-1)=y | | -9(0)=y | | x+2(9)=12 | | x+2(0)=12 | | (4x)/(8x+72)*(4+36)/4x^6 |